In vitro simulated digestion and in vivo metabolism of chlorogenic acid dimer from Gynura procumbens (Lour.) Merr.: Enhanced antioxidant activity and different metabolites of blood and urine. Issue 6 (27th September 2018) - Li, Jingfang; Qin, Yong; Yu, Xiuliang; Xiong, Zengxing; Zheng, Liufeng; Sun, Yong; Shen, Jinrong; Guo, Nansheng; Tao, Lin; Deng, Zeyuan; Liu, Xiaoru
Abstract: Gynura procumbens (Lour.) Merr. is an evergreen edible vine in southern China. The antioxidant activity and metabolites of chlorogenic acid dimer from Gynura procumbens (Lour.) Merr. were evaluated by the model of in vitro digestion and in vivo metabolomics approach, respectively. Moreover, metabolites of chlorogenic acid dimer in blood and urine of Sprague‐Dawley rats were determined by HPLC‐ESI‐QTOF‐MS/MS. In vitro digestion results suggested the antioxidant activity of the purified chlorogenic acid dimer was significantly enhanced after simulated digestion. Meanwhile, in vivo metabolism results showed that 7 and 20 new metabolites were observed in blood and urine, respectively, suggesting that hydrolysis along with methylation, glucuronidation and other reactions may all happen when the chlorogenic acid dimer entered the digestive and metabolic systems, which inducing and exhibiting various biological activities through metabolism. Practical applications: Gynura procumbens (Lour.) Merr. (GPM) is an evergreen edible vine with the effects of anticancer, anti‐inflammatory, antiviral, depressurization, and antioxidation. As a health care vegetable, it is not usually eaten in daily life. Our current study shows that chlorogenic acid dimer extracted from GPM has a significant enhanced antioxidant ability after gastro‐intestinal digestion in vitro, and their metabolites in vivo of urine is far more than that of blood, which may indicate that the chlorogenic acid dimer can be fully absorbed and decomposed through the gastro‐intestinal digestion and metabolism. Thus, GPM could be used as a functional food ingredient for antioxidant enhancement to promote the economic value. The research also provides theoretical data for the intensive processing and utilization of GPM, as well as for the relative research on digestion and metabolism of edible plants.